EIB Working Paper 2022/08 - Are EU firms climate-ready? - European Investment Bank (2022)
"This study uses unique firm-level data from EIBIS to identify EU firms' climate strategies and the firm characteristics associated with them. Through a clustering analysis, the these strategies are divided into five distinct clusters, in line with the correspondent literature. We then investigate the role of various firms' characteristics in their adoption based on a multi-logit regression. The findings show that almost half of the EU firms either adopt ""wait-and-see"" strategies or plan to invest in tackling climate change risks. More climate-friendly strategies appear to be positively associated with awareness of climate-related risks, especially with firms that see the transition to a low-carbon future as an opportunity. Similarly, those strategies are followed by large firms that are innovative, face fewer credit constraints and operate in an environment where there is a strong push for climate action from various stakeholders. These findings can guide policymakers on supporting firms' transformation to play their part, as an integral part of our society, in the road to a clean, affordable, and secure energy future."